FUZZY CONTROL INTEGRATED SINGLE STAGE ZETA-SEPIC CONVERTER FOR ROBUST EV BATTERY CHARGING - Nikhil T. Arakhrao; Prof. S. H. Thakare (International Engineering Journal For Research & Development, 2021)
Fuzzy Controllers have been proposed for physical systems which do not lend themselves to easy and accurate mathematical modelling and crisp variables, and therefore, cannot be tackled by traditional strictly analytic control design techniques. Instead, control variables are represented by fuzzy variables which let the level of uncertainty of the variables be modelled in a systematic way A single-stage-based integrated power electronic converter has been proposed for EV Battery Charging.The proposed converter achieves all modes of vehicle operation EV Battery Charging, propulsion and regenerative braking modes with wide voltage conversion ratio (M) [M < 1 as well as M > 1] in each mode. Therefore, a wide variation of battery voltage can be charged from the universal input voltage (90–260 V) and allowing more flexible control for capturing regenerative braking energy and dc-link voltage. The proposed converter has least components compared to those existing converters which have stepping up and stepping down capability in all modes. Moreover, a single switch operates in pulse width modulation in each mode of converter operation hence control system design becomes simpler and easy to implement. To correctly select the power stage switches, a loss analysis of the proposed converter has been investigated in ac/dc and dc/dc stages. Both simulation and experimental results are presented to validate the operation of the converter